Risk Factor Analysis of the Value Chain for Sawn Rubberwood Timber Exports to China - Nimsai, Suthep; Ho, Phutawan (International Journal of Supply Chain Management, 2019)
This study aims to propose risk factor analysis and to estimate how risk factors impact the average production efficiency of Thai sawn rubberwood timber exports to China as this impact could represent an aspect of the market. Data from the Risk in Value Chain concept and in-depth interviews with Thai sawn rubberwood timber exporters were used to identify the variables. The data collected from the distributed questionnaires were analyzed using exploratory factor analysis. Four significant risk factors were extracted and found to be reliable: irregularity, volatility, dependability, and ambiguity. The researchers used multiple regression analysis to estimate how risk factors impact the average production efficiency. As statistically significant results with confidence intervals of 95%, risks from irregularity and volatility were two factors that had highly negative impacts on average production efficiency. The Thai government and sawn rubberwood timber exporters could use these results as a guide to carefully develop a strategy or to plan for their future business.